Electronic origin and structural instabilities of Ti-based alloys suitable for orthopaedic implants. (March 2017) - Lekka, Ch.E.; Gutiérrez-Moreno, J.J.; Calin, M.
Abstract: We present electronic structure calculations results on Ti, Nb and TiNb model systems seeking for the electronic origin of structural instabilities. It came out that the β-Ti instability is associated with the presence of: a) degenerated states, b) few first neighbor bonds (FN) close to Fermi level (EF ), c) "critical crossing electron states" along the soft phonon directions, usually with 3deg →3dt2g transitions and d) semi-core 3p that reduce FN. In β-Nb these features are altered, while, importantly, FN homogeneous hybridizations dominate the Brillouin zone. Indeed, the amount of low energy Nb-Nb FN (even next FN) results in various Ti-Nb phases that are also correlated with the phase's coordination number. The stability of β-TiNb upon sp dopant additions and their elastic softening also follows these electronic characteristics. This approach may provide an alternative path towards the design of stable Ti-based biocompatible alloys. Graphical abstract: Highlights: Structural instability is related to 4 electronic band structure characteristics. Existence of few first neighbor bonds at Fermi level. "Critical crossing electron states" along soft phonon directions (3deg →3dt2g ). Semi-core 3p that reduce first neighbor bonds.